Cognitive Reserve Relates to Functional Network Efficiency in Alzheimer’s Disease - Weiler, Marina; Casseb, Raphael Fernandes; de Campos, Brunno Machado; de Ligo Teixeira, Camila Vieira; Carletti-Cassani, Ana Flávia Mac Knight; Vicentini, Jéssica Elias; Magalhães, Thamires Naela Cardoso; de Almeira, Débora Queiroz; Talib, Leda Leme; Forlenza, Orestes Vicente; Balthazar, Marcio Luiz Figueredo; Castellano, Gabriela (Frontiers in Aging Neuroscience, 2018)
Alzheimer’s disease (AD) is the most common form of dementia, with no means of cure or prevention. The presence of abnormal disease-related proteins in the population is, in turn, much more common than the incidence of dementia. In this context, the CR hypothesis has been proposed to explain the discontinuity between pathophysiological and clinical expression of AD, suggesting that CR mitigates the effects of pathology on clinical expression and cognition. fMRI studies of the human connectome have recently reported that AD patients present diminished functional efficiency in resting-state networks, leading to a loss in information flow and cognitive processing. No study has investigated, however, whether CR modifies the effects of the pathology in functional network efficiency in AD patients. We analyzed the relationship between CR, pathophysiology and network efficiency, and whether CR modifies the relationship between them. Fourteen mild AD, 28 amnestic mild cognitive impairment due to AD (aMCI), and 28 controls were enrolled. We used education to measure CR, CSF biomarkers to evaluate pathophysiology, and graph metrics to measure network efficiency. We found no relationship between CR and CSF biomarkers; CR was related to higher network efficiency in all groups; and abnormal levels of CSF protein biomarkers were related to more efficient networks in the AD group. Education modified the effects of tau-related pathology in the aMCI and mild AD groups. Although higher CR might not protect individuals from developing AD pathophysiology, AD patients with higher CR are better able to cope with the effects of pathology – presenting more efficient networks despite pathology burden. The present study highlights that interventions focusing on cognitive stimulation might be useful to slow age-related cognitive decline or dementia and lengthen healthy ageing.